Biochemical changes in guava (Psidium guajava) cv. Allahabad Safeda fruits as a function of maturity stages - RAJKUMAR, RAJKUMAR; KAUR, GURPREET; MANN, ANITA; LATA, CHARU; SINGH, ANSHUMAN; KUMAR, ASHWANI (The Indian Journal of Agricultural Sciences, 2016)
The effects of maturity stage and harvesting season were investigated on fruit quality attributes like total antioxidant activity (DPPH), total flavanoids, total phenolics, H2O2 scavenging activity and ascorbic acid content in fruits of guava (Psidium guajava L) cv. Allahabad Safeda obtained from ICAR-CSSRI, Karnal guava orchard. Based on fruit colour and firmness, fruits representing four distinct maturity stages, i.e., immature, mature, ripe and overripe; and two crop seasons, i.e. summer and winter; were selected for biochemical analysis. Significant differences were observed in the antioxidant activities and chemical composition of the fruits at different maturity stages during summer and winter seasons of harvesting. Guava fruits collected in winter season showed higher antioxidant activity, flavanoids content, total phenolics, H2O2 scavenging activity and ascorbic acid content as compared with summer season fruits. Immature fruits had higher antioxidant activity, flavanoids content and total phenol content (49.35%, 26.98 mg/100g and 24.84 mg TA/g) during both the seasons than mature (40.02%, 24.22 mg/100g and 23.95 mg TA/g), ripe (31.76%, 20.54 mg/100g and 23.62 mg TA/g) and overripe fruits (25.7%, 17.04 mg/100g and 23.17 mg TA/g), respectively. In contrast, H2O2 scavenging activity increased with maturity in both the seasons and was found to be maximum in over ripe fruits (501.48 Î¼mol/g). Ripe fruits had the highest ascorbic acid content (205.03 mg/100 g) that considerably decreased in over ripe fruits (137.25 mg/100 g). These findings indicated that both maturity stage and harvesting season significantly influenced fruit biochemical composition in guava cv. Allahabad Safeda. Season and maturity stage-specific variations in fruit quality assume significance from post-harvest management and consumer preference perspectives.